Awareness workplace hazards in selected university's staff / Norhidayah Nazari - Norhidayah, Nazari (2018)
Working condition such as work environment, work organization, tasks and work place play a crucial role to the employees in performing their daily routines. These elements may simply determine the level of employees‟ motivation, performance and productivity. A good working condition in an organization is considered to cover health and safety issues. Therefore, this study is conducted to assess the awareness of workplace hazards in selected university‟s workers, namely University A. Views from the academician and non-academician are been focused by using self-administrative questionnaire and observation through site visit in few areas such car park, elevator, informal learning spaces and office. The details of the awareness towards hazards in workplace that were taken into considerations were policy and procedures; environments and equipment; information and trainings as well as attitudes and commitments. The findings indicate that awareness level among staff towards hazards in workplace is high and there is a significant relationship among the studied variables which directly influenced the result of study. The study suggests that it is vital for the management to participate and promote safety culture in the workplace.